A New Account of Britain’s Economic Development - Borus, György (Hungarian Journal of English and American Studies, 2020)
Book review: Broadberry, Stephen, Bruce M. S. Campbell, Alexander Klein, Mark Overton, and Bas van Leeuwen. British Economic Growth, 1270-1870. Cambridge: CUP, 2015. 461 pages. ISBN 978-1-107-67649-7. Pbk. £25.